Focal 123I-FP-CIT SPECT Abnormality in Midbrain Vascular Parkinsonism - Solla, Paolo (Hindawi Publishing Corporation, 2015)
Cerebrovascular diseases are considered among possible causes of acute/subacute parkinsonism, representing up to 22% of secondary movement disorders. In cases of suspected vascular parkinsonism (VP), dopamine transporter SPECT has been highly recommended to exclude nigrostriatal dopaminergic degeneration. We report the case of a hemiparkinsonism related to a left midbrain infarct with focal lateralized putaminal abnormalities at 123I-FP-CIT SPECT imaging. The asymmetric uptake at dopamine transporter SPECT was different to findings commonly observed in typical PD pattern, because the ipsilateral striatum, in opposite to idiopathic PD, showed normal tracer binding. However, this selective parkinsonism after infarction of the midbrain was responsive to levodopa. In conclusion, we retain that there is a need of more functional imaging studies in VP addressed to a more consistent classification of its different clinical forms and to a better understanding of the adequate pharmacological management.